B Cells on the Stage of Inflammation in Juvenile Idiopathic Arthritis: Leading or Supporting Actors in Disease Pathogenesis? - Moura, Rita A.; Fonseca, João Eurico (Frontiers in Medicine, 2022)
Juvenile idiopathic arthritis (JIA) is a term that collectively refers to a group of chronic childhood arthritides, which together constitute the most common rheumatic condition in children. The International League of Associations for Rheumatology (ILAR) criteria define seven categories of JIA: oligoarticular, polyarticular rheumatoid factor (RF) negative (RF-), polyarticular RF positive (RF+), systemic, enthesitis-related arthritis, psoriatic arthritis and undifferentiated arthritis. The ILAR classification includes persistent and extended oligoarthritis as subcategories of oligoarticular JIA, but not as distinct categories. JIA is characterized by a chronic inflammatory process affecting the synovia that begins before the age of sixteen and persists at least six weeks. If not treated, JIA can cause significant disability and loss of quality of life. Treatment of JIA is adjusted according to the severity of the disease as combinations of non-steroidal anti-inflammatory drugs (NSAIDs), synthetic and/ or biological disease modifying anti-rheumatic drugs (DMARDs). Although the disease etiology is unknown, disturbances in innate and adaptive immune responses have been implicated in JIA development. B cells may have important roles in JIA pathogenesis through autoantibody production, antigen presentation, cytokine release and/ or T cell activation. The study of B cells has not been extensively explored in JIA, but evidence from the literature suggests that B cells might have indeed a relevant role in JIA pathophysiology. The detection of autoantibodies such as antinuclear antibodies (ANA), RF and anti-citrullinated protein antibodies (ACPA) in JIA patients supports a breakdown in B cell tolerance. Furthermore, alterations in B cell subpopulations have been documented in peripheral blood and synovial fluid from JIA patients. In fact, altered B cell homeostasis, B cell differentiation and B cell hyperactivity have been described in JIA. Of note, B cell depletion therapy with rituximab has been shown to be an effective and well-tolerated treatment in children with JIA, which further supports B cell intervention in disease development.